A Medicago truncatula rdr6 allele impairs transgene silencing and endogenous phased siRNA production but not development. Issue 9 (24th July 2014) - Bustos‐Sanmamed, Pilar; Hudik, Elodie; Laffont, Carole; Reynes, Christelle; Sallet, Erika; Wen, Jiangqi; Mysore, Kirankumar S.; Camproux, Anne‐Claude; Hartmann, Caroline; Gouzy, Jérome; Frugier, Florian; Crespi, Martin; et al.
Summary RNA‐dependent RNA polymerase 6 (RDR6) and suppressor of gene silencing 3 (SGS3) act together in post‐transcriptional transgene silencing mediated by small interfering RNAs (siRNAs) and in biogenesis of various endogenous siRNAs including the tasiARFs, known regulators of auxin responses and plant development. Legumes, the third major crop family worldwide, has been widely improved through transgenic approaches. Here, we isolated rdr6 and sgs3 mutants in the model legume Medicago truncatula. Two sgs3 and one rdr6 alleles led to strong developmental defects and impaired biogenesis of tasiARFs. In contrast, the rdr6.1 homozygous plants produced sufficient amounts of tasiARFs to ensure proper development. High throughput sequencing of small RNAs from this specific mutant identified 354 potential MtRDR6 substrates, for which siRNA production was significantly reduced in the mutant. Among them, we found a large variety of novel phased loci corresponding to protein‐encoding genes or transposable elements. Interestingly, measurement of GFP expression revealed that post‐transcriptional transgene silencing was reduced in rdr6.1 roots. Hence, this novel mis‐sense mutation, affecting a highly conserved amino acid residue in plant RDR6s, may be an interesting tool both to analyse endogenous pha‐siRNA functions and to improve transgene expression, at least in legume species.